A Case of Acute Lymphocytic Leukemia relapsed with Obstructive Jaundice - Ariga, Takamitsu; Yoshimura, Seiji; Oshima, Ikuya; Shinoto, Koichi; Ozaki, Masahiko; Kinoshita, Hirohisa (Nippon Shokaki Geka Gakkai zasshi, 2005)
A 38-year-old woman admitted for jaundice and treated for acute lymphocytic Leukemia was found in abdominal ultrasonography and abdominal computed tomography to have a mass in the pancreas head. Based on her history, we diagnosed intraperitoneal relapse of leukemia and conducted cholecystectomy and lymphadenectomy. Microsopically. The gall bladder was confirmed to have gangrenous cholecystitis and lymph nodes showed the metastasis of leukemia. The woman died about 1 year after sugery due to meningial infiltration.